The Role of Baitul Maal (BMN) East Java Pamekasan Pegantenan Branch In Improving Community Welfare - Moh. Supriyadi (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
This Baitul Maal has existed since the time of the Prophet Muhammad. However, the most visible role since the time of the companions of the Prophet was during the time of Abu Bakr as Siddiq to the time of Ali Bin Abi Thali. Where is the role and function of the Baitul Maal at the time of the friends not only as a financial institution that manages the economy in a simple way, but instead becomes an institution that takes care of all state financial matters as well as a financial institution that manages all state assets. Then the development of this institution is now the Baitul Maal which is complete as a financial institution in order to be part of activities for the welfare of the people's lives.